The Effect of Work Culture and Physical Skills Competence on Employee Performance at PT. Khong Guan Biscuit Factory Indonesia Ltd - Endang Sugiarti; Hikmatul Ulum Alawiyah; Wahyudi Wahyudi (Program Doktor Ilmu Manajemen, Universitas Pasundan, Indonesia, 2022)
The objectives of this study are: 1) To determine the effect of work culture on employee performance at PT. Khong Guan Biscuit Factory Indonesia Ltd. 2) To determine the effect of physical skill competence on employee performance at PT. Khong Guan Biscuit Factory Indonesia Ltd.. 3) To determine the effect of work culture and physical skills competence together on employee performance at PT. Khong Guan Biscuit Factory Indonesia Ltd. This research approach is quantitative, descriptive and associative. The population in this study were 50 PT. Khong Guan Biscuit Factory Indonesia Ltd. In this study, the sampling technique used is non-probability sampling with the technique taken is saturated sampling (census), a sample of 50 respondents was taken at PT. Khong Guan Biscuit Factory Indonesia Ltd. The results of this study indicate that: 1) There is an influence of work culture on employee performance. 2) There is an influence of physical skill competence on employee performance. 3) There is an influence of work culture and physical skill competence together on employee performance.